85.5k views
4 votes
Which is a solution to (x – 3)(x + 9) = –27?

x = –9
x = –3
x = 0
x = 6

2 Answers

3 votes

Answer:

C: x = 0

There is no solution.

User Soyeon
by
5.2k points
2 votes

Answer:

x = 0

Explanation:

Since the product is not equal zero, we need to multiply both parenthesis first:


(x-3)(x+9) =-27


x*x+x*9+(-3)*x+(-3)*9=27


x^2+9x-3x-27=27


x^2+6x-27=27

Add 27 from both sides:


x^2+6x-27+27=-27+27


x^2-6x=0

Factor
x out:


x(x+6)=0

Apply the zero product:


x=0,x+6=0


x=0,x=-6

The solutions of the equation are
x=0 and
x=-6.

We can conclude that the correct answer is x = 0.

User Mike Putnam
by
4.8k points